Optimization of hybrid manufacturing for surface quality, material consumption and productivity improvement - Grguraš, Damir (Strojniški vestnik, 2017)
This paper presents hybrid manufacturing process of 3D printing and milling. Fused deposition modeling (FDM) has been applied to improve product manufacturing performance, afterwards, milling was used to improve outer surface roughness. Today's FDM systems rely on the use of standard nozzle size with a diameter of Dsub1 = 0.4 mm. To achieve shorter production times a bigger nozzle size (diameter Dsub2 = 1.1 mm) has been used in this research. Optimization of technological parameters of hybrid manufacturing was carried out according to the minimal time of production, a minimal final surface roughness and minimal usage of material. In addition, these results were compared with optimal results obtained with the standard nozzle size. Significantly shorter production time, without affecting surface quality, was achieved when using bigger nozzle size.
Keywords: ciljno nalaganje taljenega polimera; empirično modeliranje in optimizacija; frezanje; hibridna izdelava; material PLA; metodologija odzivne površine; načrtovanje eksperimentov